Cash Flow Diagramming In Line of Balance Technique by Using Matlab - Tabakh, Alireza Bajgiran (Eastern Mediterranean University (EMU), 2010)
Contractors often encounter with repetitive types of projects that contain several identical or similar units. These multi-unit projects are characterized by repeating activities. The known construction planning techniques such as Bar Chart and Network Diagramming method are not suitable and sufficient for repetitive types of projects. For these kinds of projects, Line of Balance planning techniques (LOB) are mainly used. For all construction projects, costs and times must be monitored and controlled, whether from the point of view of an owner, a project manager or a contractor. Cash flow is another extremely important issue, which the contractors and owners must be sensitive if they want to survive. However although there are a number of software for the Line of Balance planning technique, developing a computerized method capable of obtaining Line of Balance and drawing the LOB graphs and additionally obtains cash flow and drawing the cash flow diagrams is essential for contractors and owners. Furthermore, preparing Line of Balance scheduling and preparing the financial statements for the method is a time consuming process which can be a source of errors. The primary goal of this study was to develop a computer program by using Matlab package in Line of Balance method for clients, contractors and project managers which can be used effectively in construction projects. The Line of Balance method can be obtained easily, accurately in just few minutes. Moreover, the program has capability of obtaining cash flow and drawing cash flow diagrams for different periods of time, phase or section of project. By using the software the cash flow is determined, cumulative, daily, weekly and monthly cash flow diagrams are prepared accordingly. In order to evaluate the developed program, a Villa housing project is selected as a case study. Entering the Line of Balance input data and preparing Line of Balance table are done in less than one hour by using the software. The Line of Balance graphs, cash flow and cash flow diagrams are prepared automatically in just few seconds. However, it takes several hours to prepare them manually without using a software. The Line of Balance table is prepared and calculated by Microsoft Excel to compare the results with the developed software. The exact and accurate results were obtained by using the developed program compared to Microsoft Excel program.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2010. Supervisor: Prof. Dr. Tahir Çelik.
Keywords: Civil Engineering; Line of Balance technique - Cash flow - Matlab package - Microsoft Excel